The Feasibility of Gurindam Writing Teaching Materials Based on Narrative Text for Grade X Using Construct Validity - Welsi Damayanti; Rika Widawati; Siti Hamidah (Raja Zulkarnain Education Foundation, 2025)
In 2024, an integrated teaching material for writing Gurindam based on a narrative text for grade X of high school was produced, containing 70 A4 pages. This manual teaching material contains three integrated learning units using a constructivist approach, namely integrated learning with expository text, prophetic short story text, and procedural text. This study aims to describe: 1) the feasibility of the content of the integrated teaching material for writing gurindam based on narrative text from a construct validity perspective; 2) the feasibility of the presentation of the integrated teaching material for writing gurindam based on narrative text using a construct validity perspective; 3) the feasibility of the language of the integrated teaching material for writing gurindam based on narrative text from a construct validity perspective. This research, which uses a quantitative descriptive method, took place in the even semester of the 2024/2025 academic year. Integrated teaching material data were collected using observation guidelines and checklists with a time triangulation system. The feasibility of the teaching material was determined by each of a material validator, method validator, and practitioner validator to assess each indicator using a value scale of 1-4. The results of the study: 1) the feasibility of the content of integrated teaching materials for writing gurindam based on narrative text from the perspective of construct validity is categorized as very feasible; 2) the feasibility of the presentation of integrated teaching materials for writing gurindam based on narrative text from the perspective of construct validity is categorized as very feasible; 3) the feasibility of the language of integrated teaching materials for writing gurindam based on narrative text from the perspective of construct validity is categorized as very feasible.